Prevalence of depression and its associated risk factors among children and adolescent screened at a tertiary care hospital - Abimannan, Vedapriya; Pothapregada, Sriram; Varadhan, Balachandar Bangalore; Abimannan, Shanmuga Vadivu; Amisha (International Journal of Contemporary Pediatrics, 2024)
Background: Depression in children and adolescents has been increasing worldwide especially in the adolescence. Despite its high prevalence and its substantial impact, the detection and its treatment in primary care setting have been suboptimal. To estimate the prevalence of depression among 8-17 years attending OPD at a tertiary care hospital and the risk factors associated with it. Methods: A cross-sectional study done among 400 participants of 08 to 17 years of age presenting to Pediatric and Medicine Outpatient departments of a Tertiary Care Hospital at Puducherry. A three-step process on diagnosis was involved. Step 1 included screening for psychiatric morbidities using Tamil and English version of Strengths and Difficulties Standardized Questionnaire. Those scoring above 19 were subjected to a second screening test for depression using Centre for Epidemiological Studies Depression scale for Children. All these participants were referred for psychiatric assessment irrespective of their CES-DC score for diagnosis. The data was analysed by descriptive statistics. Results: Among the study population, 49 (12.25%) participants had depression. Among the participants with 8 to 12 years of age, 10 (5%) participants had depression. Among the participants with aged 13 to 17 years, 39 (19.5%) participants had depression. The risk factors significantly associated with depression include age group, friends, sickness, constant fidgeting/squirming, temper tantrum, bullying, addiction in parents, parent education. Conclusion: Owing to the prevalence of depression in our study especially in the late adolescent, the importance is to be given for early diagnosis and appropriate management.